The Causative Factor of Semantic Error in the Students’ Assignment Papers at Widya Mandala Madiun Catholic University-Indonesia - Septiani, Pramudita; Suwandi, Sarwiji; Setiawan, Budhi (International Journal of English Literature and Social Sciences (IJELS), 2019)
This study aims to explain and describe the causative factors of language errors in semantic on the students’ assignment papers. The subjects of this study were students who had taken MKU-BI (Indonesian General Course) courses at Widya Mandala Madiun Catholic University, who came from various disciplines. This research uses descriptive qualitative research, and observation and field note techniques as data collection techniques. The results of the data are documents (in the form of students’ assignment papers) and students’ interviews. Data analysis techniques used in this study is sharing methods or distribution methods with advanced techniques in the form of extension (expansion) techniques and changing forms. The conclusions of the study are the causative factors of language errors at the syntactic level caused by (1) Affected by the language that was mastered first, (2) Language users’ lack of understanding over the use of the language, (3) Language teaching that is less precise or imperfect.